SPECIFICITY AND SOCIAL MANIFESTATIONS OF THE FRENCH LANGUAGE IN THE SPEECH OF YOUNG PEOPLE (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the functioning of the French language among young people and its social manifestations. Particular attention is paid to such phenomena as verlan, slang, borrowings, and the influence of digital communication. Based on sociolinguistic and contextual analysis, the mechanisms of the formation of the youth linguistic space are identified. The results of the study demonstrate that youth speech is a dynamic system reflecting the processes of globalization, mediatization, and sociocultural identification.
Keywords: French, youth language, verlan, slang, sociolinguistics, borrowings, digital communication.